Low-toxicity nylon material modified composition as well as preparation method and application thereof
By leveraging the synergistic effect of bio-based polyamide, surface-functionalized nano-chitosan, and bilayer wall material natural polyphenol microcapsules, the problems of insufficient cytotoxicity and biocompatibility of nylon materials in skin contact products are solved, achieving low toxicity and skin-friendly effects, suitable for long-term skin contact products such as watch straps.
Patent Information
- Application Number
- CN202511433431.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-09
- Publication Date
- 2025-12-19
AI Technical Summary
Existing nylon materials suffer from high cytotoxicity, poor biocompatibility, and insufficient skin-friendliness in skin contact applications, especially in products that require prolonged skin contact such as watch straps. Traditional improvement methods have failed to effectively address the challenges of material biosafety and skin comfort.
A low-toxicity nylon material modified composition is used, comprising bio-based polyamide, surface-functionalized nano-chitosan, bilayer wall material natural polyphenol microcapsules, and interface synergistic locking agent. Through covalent grafting and melt blending techniques, the synergistic effect of the components is achieved, enhancing the material's low toxicity and skin-friendliness.
The material achieves low toxicity and high biocompatibility, can actively adsorb harmful substances, continuously release antioxidant and soothing factors, improve the comfort of long-term wear and skin health, and has high binding strength of functional components to prevent loss.
Smart Images

Figure BDA0005626151830000111 
Figure BDA0005626151830000121 
Figure BDA0005626151830000151
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of high polymer material modification, and particularly relates to a low-toxicity nylon material modification composition and a preparation method and application thereof. BACKGROUND
[0002] Polyamide (PA), commonly known as nylon, is widely used in various fields due to its excellent mechanical properties, wear resistance, chemical corrosion resistance, and easy processing, including products that are in long-term contact with human skin, such as clothing fibers, watch bands, smart wearable device housings and wristbands, and components of certain medical devices.
[0003] However, in these skin contact application scenarios, traditional nylon materials, especially those synthesized based on petrochemical raw materials, often face challenges in biocompatibility. Unreacted monomers, oligomers, degradation products generated during processing, or certain additives that may exist in the material can slowly migrate out during long-term contact with the skin. These migrating substances can have certain toxic effects on human cells, causing skin irritation, allergic reactions, or other discomfort, thereby limiting their application in high-end or sensitive skin contact products and posing potential risks to the wearer.
[0004] Although there have been some attempts in the industry, such as selecting higher purity raw materials or improving polymerization processes to reduce harmful residues, or adding inert fillers to the material to improve certain physical properties, these methods often fail to fundamentally solve the inherent cytotoxicity problem of the material and fail to actively endow the material with skin-friendly properties. There are still obvious technical bottlenecks in improving the biological safety of existing nylon materials, especially in reducing cytotoxicity, enhancing skin compatibility, and providing active skin soothing or protective functions. Therefore, the development of a new type of nylon material with excellent low toxicity, high biocompatibility, and the ability to actively improve the skin contact experience is of great practical significance to meet the growing demand for health and comfort. SUMMARY
[0005] The present application aims to solve the technical problems of high cytotoxicity, poor biocompatibility, and insufficient skin friendliness of existing nylon materials, especially when used in long-term skin contact products such as watch bands. In particular, to address the low pass rate of cytotoxicity tests in biocompatibility tests and the tendency to cause discomfort when wearing traditional nylon watch bands, a nylon material modification composition with excellent low toxicity, high biocompatibility, and active skin-friendly properties is provided, as well as a preparation method and application thereof.
[0006] To achieve the above purpose, the present application is implemented by the following technical solutions: The first aspect of the present application provides a low-toxicity nylon material modified composition, which comprises, by weight percentage: 70-90wt% of bio-based polyamide; 2-10wt% of surface-functionalized nanochitosan; 3-15wt% of double-walled material natural polyphenol microcapsule; 0.1-0.5wt% of interfacial synergistic locking agent.
[0007] In the present application, the components synergistically work together to endow the composition with excellent low toxicity and skin friendliness: The bio-based polyamide, as the matrix resin, is itself derived from renewable resources, and generally has lower unreacted monomer residues and better basic biocompatibility than traditional petroleum-based nylon, laying the foundation for the low toxicity of the overall composition.
[0008] The surface-functionalized nanochitosan plays multiple key roles in the present composition: Firstly, its nanoscale size (preferably an average particle size of 50-200 nm) provides a large specific surface area, enhancing its interaction with the matrix and other components and the efficiency of its own functions.
[0009] Secondly, chitosan itself has good biocompatibility, biodegradability, and certain natural mild antibacterial properties.
[0010] The core is its surface functionalization: the present application preferably treats nanochitosan with N-carboxymethylation, which not only improves its water dispersibility and biocompatibility, but more importantly introduces active carboxyl groups, providing sites for subsequent functionalization grafting. Subsequently, the N-carboxymethylated nanochitosan is covalently grafted with an aminated β-cyclodextrin derivative (such as mono-6-amino-6-deoxy-β-cyclodextrin). β-cyclodextrin has a unique molecular structure of a hydrophobic inner cavity and a hydrophilic outer edge, and its inner cavity can selectively include or adsorb trace amounts of harmful small molecules that may exist in the nylon matrix, such as residual monomers, oligomers, migration of certain additives, or early degradation products during material use, through host-guest interactions. This grafting enables nanochitosan to have the ability to target adsorption and fixation of harmful substances, like setting up a micro-purifier inside the material, thereby actively reducing the cytotoxicity of the material, which is significantly different from traditional inert fillers or simple physical adsorption.
[0011] The double-walled material natural polyphenol microcapsule provides the composition with persistent antioxidant and skin soothing functions: Its active core is natural polyphenol (such as grape seed extract proanthocyanidin or green tea extract tea polyphenol), which has strong free radical scavenging ability and known skin soothing and anti-inflammatory potential.
[0012] The double-layer wall material structure is the key to realize its function and protect its activity: The inner layer wall material is preferably formed by gelatin and gum arabic through complex coacervation. This natural high molecular wall material can effectively encapsulate and protect natural polyphenols, preventing premature inactivation during the initial processing or storage period.
[0013] The outer layer wall material is preferably composed of biodegradable polyester (such as polycaprolactone PCL or polylactic acid PLA). Selecting biodegradable polyester with a specific glass transition temperature (Tg) as the outer layer can achieve gradient release or on-demand release of natural polyphenols during nylon processing and when the final product is worn (e.g. affected by body temperature, sweat microenvironment). This means that polyphenols will not be released quickly at once, but can be continuously and slowly migrated to the material surface or near-surface, forming a dynamic in-situ antioxidant network at the skin contact interface, long-term resisting material aging and oxidative stress caused by the external environment to the skin, while exerting its soothing effect.
[0014] The introduction of the interface synergistic locking agent (preferably citric acid or its derivatives that can be formed under processing conditions such as citric anhydride, or polyol esters with specific structures) aims to enhance the stability and durability of each functional component in the nylon matrix: the locking agent can form a micro-bridge or anchor point at the component interface during melt blending processing by moderate chemical reactions (such as esterification, amidation) or strong physical interactions (such as hydrogen bond network) between its functional groups (such as carboxyl, hydroxyl) and the terminal amino or carboxyl groups of biobased polyamide, the amino / hydroxyl / carboxyl groups on the surface of surface-functionalized nanochitosan, and the functional groups possibly exposed on the surface of microcapsule wall material. This locking effect significantly improves the binding strength of functional nanochitosan and polyphenol microcapsules in the matrix, effectively preventing their premature migration and loss from the material under long-term use, sweat soaking or physical friction conditions, thereby ensuring the long-term effectiveness of the composition's low toxicity and skin-friendly function.
[0015] Preferably, the biobased polyamide is selected from at least one of biobased polyamide 11 or biobased polyamide 1010, both of which are mature biobased engineering plastics with good overall performance.
[0016] Preferably, the aminated β-cyclodextrin derivative is mono-6-amino-6-deoxy-β-cyclodextrin, which has a clear reaction site and is easy to graft.
[0017] Preferably, the natural polyphenol is selected from at least one of grape seed extract procyanidin or green tea extract tea polyphenol, which is a recognized high-efficiency and safe natural antioxidant.
[0018] Preferably, the biodegradable polyester is selected from at least one of polycaprolactone or polylactic acid, which has good biocompatibility and controllable degradation / release characteristics.
[0019] Preferably, the composition can further comprise 0.2-1.0wt% of biocompatible lubricant (such as medical grade calcium stearate or carnauba wax) to improve the processing performance and further reduce thermal degradation during processing; and / or 0-2.0wt% of biocompatible color masterbatch (selected from the grades that have passed medical or food contact certification) to meet the color requirements of the product, while ensuring that no additional cytotoxicity risk is introduced.
[0020] The second aspect of the present application provides a method for preparing the low-toxicity nylon material modified composition described above, comprising the following steps: (i) mixing the bio-based polyamide, the surface-functionalized nanochitosan, the double-layer wall material natural polyphenol microcapsule, and the interfacial synergistic locking agent, together with the optional biocompatible lubricant and / or biocompatible color masterbatch, to obtain a mixture; (ii) melt blending and extruding the mixture through a twin-screw extruder.
[0021] The preparation method can ensure the uniform dispersion of nanoscale fillers and microcapsules in the polyamide matrix through the strong shearing and mixing effects of the twin-screw extruder. More importantly, during the melt blending process, the precisely controlled temperature and shearing conditions help the interfacial synergistic locking agent to function in situ, promoting the formation of interfacial reactions or strong interactions with each component. At the same time, this process can also cause controllable micro-influences on the outer layer of the double-layer wall material microcapsule, creating conditions for subsequent gradient release.
[0022] Preferably, in step (ii), the temperature of the melting zone of the twin-screw extruder is controlled at 210-230℃, which can ensure the sufficient plasticization of the bio-based polyamide and the moderate reaction of the interfacial locking agent, while minimizing the excessive destruction of heat-sensitive active ingredients such as natural polyphenols. A vacuum exhaust is set at the rear part of the melting section to effectively remove moisture, small molecule volatiles, and reaction byproducts that may be generated during processing, improving the purity and performance stability of the final product.
[0023] Preferably, before step (i), the method further comprises a careful preparation step for the key functional components: (a1) N-carboxymethylizing the nanochitosan to obtain N-carboxymethyl nanochitosan; (a2) covalently grafting the N-carboxymethyl nanochitosan with an aminated β-cyclodextrin derivative under the catalysis of EDC·HCl and NHS to obtain the surface functionalized nanochitosan. These steps ensure the construction of the targeted adsorption function of the nanochitosan.
[0024] (b1) coating natural polyphenols with gelatin and gum arabic as inner wall materials by complex coacervation to obtain inner-layer polyphenol microcapsules; (b2) coating the inner-layer polyphenol microcapsules with a biodegradable polyester as an outer wall material to obtain the double-layer wall natural polyphenol microcapsules. These steps ensure the effective protection of the natural polyphenols and the formation of a controllable release structure (double-layer wall).
[0025] The specific preparation method of the above functional components is an important guarantee for achieving the predetermined functions and the overall technical effects of the present application.
[0026] The third aspect of the present application provides the use of the above low-toxicity nylon material modification composition in the preparation of skin contact products.
[0027] Due to the synergistic effect of the nylon material modification composition of the present application through multiple functional components, the comprehensive effects of actively adsorbing harmful substances, continuously releasing antioxidant soothing factors, and long-acting locking of functional components are achieved, thus significantly improving the cytotoxicity, irritation, and sensitization, and improving the comfort and skin health during long-term wear.
[0028] Preferably, the skin contact product is a watchband, a smart wearable device wristband, or an elastic woven belt of close-fitting clothing, etc. which needs to be in long-term and direct contact with the human skin.
[0029] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application reduces potential cytotoxic substances from the source and process by using bio-based nylon and introducing surface functionalized nanochitosan with the ability to target and adsorb harmful small molecules.
[0030] 2. The double-layer wall natural polyphenol microcapsules of the present application can continuously release natural polyphenols with antioxidant and soothing effects, directly improving the interaction between the material and the skin, and reducing skin discomfort that may be caused by long-term wear.
[0031] 3. The application of the interfacial synergistic locking agent enhances the binding firmness of the functional additives in the nylon matrix, making them less likely to be lost due to sweat, friction, etc., ensuring the durability of the low toxicity and skin-friendly function.
[0032] 4. The functional components of the present application achieve the synergistic effect of multiple mechanisms such as targeted adsorption, gradient release, and interfacial locking, achieving technical effects that cannot be achieved by single modification means.
[0033] 5. The modified nylon material obtained by the present application has excellent comprehensive performance, and is particularly suitable for various long-term skin contact products with high requirements for biological safety and skin comfort. DETAILED DESCRIPTION
[0034] The present application will be further described in detail below in conjunction with examples.
[0035] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0036] Example 1: 1. Preparation of surface-functionalized nanochitosan (TA-NC-1) (1) 3.0 g of chitosan (90% deacetylation, viscosity-average molecular weight 2.0 x 10 5 Da) was dissolved in 1000 mL of 1.5% (v / v) aqueous acetic acid. Under stirring at 750 rpm, 1.0% (w / v) aqueous sodium tripolyphosphate was added dropwise, with a mass ratio of TPP to chitosan of 1:6. Stirring was continued for 0.75 hours. Ultrasonic treatment (22.5 kHz, 300 W, 20 minutes, ice bath). Centrifugal collection, water washing.
[0037] (2) The wet nanochitosan obtained in step (1) (about 1.5 g dry weight) was dispersed in 150 mL of isopropanol-water (volume ratio 3:1). 2.0 times the molar amount of chitosan amino of monochloroacetic acid was added. 20% (w / v) aqueous NaOH was added dropwise under ice bath to adjust the pH to 10.0. Reaction at 55°C water bath for 4.5 hours. Adjust the pH to 7.0 with dilute hydrochloric acid, and wash with ethanol.
[0038] (3) 1.0 g of dry N-carboxymethyl nanochitosan was dispersed in 100 mL of pH 5.5 MES buffer. 1.0 times the molar amount of carboxyl on N-carboxymethyl nanochitosan of mono-6-amino-6-deoxy-β-cyclodextrin was added. 2.0 times the molar amount of carboxyl of EDC·HCl and 1.0 times the molar amount of carboxyl of NHS were added. Stirring at room temperature (25°C) for 24 hours in the dark. Dialysis, freeze-drying, and TA-NC-1 powder was obtained.
[0039] 2. Preparation of double-walled material natural polyphenol microcapsules (DR-PM-1) (1) Weigh 10.0 g of gelatin and 10.0 g of gum arabic, and dissolve them separately in 200 mL of deionized water at 50 °C. Disperse 3.5 g of grape seed extract proanthocyanidins (OPC, polyphenol content ≥95%) in 50 mL of ethanol-water (volume ratio 1:2). Emulsify the OPC dispersion into the gelatin solution under 7500 rpm shear. Add the gum arabic solution. Adjust the pH to 4.0 with 10% (v / v) acetic acid and stir at 40 °C for 1.5 hours. Cool to 8 °C and maintain for 0.75 hours. Centrifuge, wash with water, and freeze-dry.
[0040] (2) Dissolve 7.5 g of PCL (M_n = 80,000 g / mol, T_g = -60℃) in 150 mL of dichloromethane. Add 2.0 g of the dried inner layer microcapsules obtained in step (1) and disperse by ultrasonication (150 W, 10 min). Coating by solvent evaporation: stir at 400 rpm for 8 hours at room temperature. Vacuum dry (32.5℃, 18 hours). Grind and sieve to obtain DR-PM-1 powder.
[0041] 3. Preparation of modified compositions for low-toxicity nylon materials (1) Raw material pretreatment: Bio-PA11 ( BMNO P40 TLD was vacuum dried at 90°C for 18 hours. TA-NC-1 and DR-PM-1 were vacuum dried at 55°C for 5 hours. Citric acid (monohydrate, food grade) was used as is. Calcium stearate (pharmaceutical grade) was dried at 70°C for 3 hours.
[0042] (2) Component composition (by weight percentage): Bio-PA11: 81.4 wt% TA-NC-1: 6.0 wt% DR-PM-1: 12.0wt% Citric acid: 0.3wt% Calcium stearate: 0.3 wt% (3) Mixing: Place all the above components in a high-speed mixer and mix at 1200 rpm for 12 minutes.
[0043] (4) Twin-screw extrusion blending: A co-rotating twin-screw extruder (L / D = 44) was used. Temperature settings for each zone (from feed inlet to die): 192℃ / 202℃ / 215℃ / 220℃ / 222℃ / 218℃ (vacuum exhaust port, vacuum degree 0.085MPa) / 212℃ / 210℃. Screw speed: 230rpm.
[0044] (5) Cooling and pelletizing: The extruded strips are cooled in a water tank (water temperature 25℃) and then cut into 3mm long pellets by a pelletizer.
[0045] (6) Final product drying: The obtained granules were dried at 80 °C under vacuum for 8 hours.
[0046] Example 2: 1. Preparation of surface-functionalized nanochitosan (TA-NC-2) (1) 2.0 g of chitosan (85% deacetylation, viscosity-average molecular weight 1.5 x 10 5 Da) was dissolved in 1000 mL of 1.0% (v / v) aqueous acetic acid. Under stirring at 500 rpm, 0.5% (w / v) aqueous sodium tripolyphosphate was added dropwise, with a mass ratio of TPP to chitosan of 1:8. Stirring was continued for 0.5 hours. Ultrasonic treatment (20 kHz, 200 W, 10 minutes, ice bath). Centrifugal collection, water washing.
[0047] (2) The wet nanochitosan obtained in step (1) (about 1.0 g dry weight) was dispersed in 100 mL of isopropanol-water (volume ratio 1:1). 1.0 times the molar amount of the amino groups of chitosan was added of monochloroacetic acid. 10% (w / v) aqueous NaOH was added dropwise under ice bath to adjust the pH to 9.0. The reaction was carried out at 45 °C water bath for 3 hours. The pH was adjusted to 7.0 with dilute hydrochloric acid, and ethanol was used for washing.
[0048] (3) 1.0 g of dried N-carboxymethyl nanochitosan was dispersed in 100 mL of MES buffer at pH 5.0. 0.5 times the molar amount of the carboxyl groups of N-carboxymethyl nanochitosan was added of mono-6-amino-6-deoxy-β-cyclodextrin. 1.5 times the molar amount of the carboxyl groups was added of EDC-HCl and 0.8 times the molar amount of the carboxyl groups was added of NHS. Stirring was carried out at room temperature (20 °C) for 18 hours in the dark. Dialysis, freeze-drying, TA-NC-2 powder was obtained.
[0049] 2. Preparation of double-walled material natural polyphenol microcapsules (DR-PM-2) (1) 10.0 g of gelatin and 10.0 g of gum arabic were weighed and dissolved in 200 mL of deionized water at 45 °C, respectively. 2.0 g of green tea extract polyphenols (EGCG content ≥ 90%) was dissolved in 50 mL of aqueous solution. Under shearing at 5000 rpm, the polyphenol solution was added to the gelatin solution for emulsification. The gum arabic solution was added. The pH was adjusted to 3.8 with 10% (v / v) acetic acid, and stirring was carried out at 35 °C for 1 hour. The temperature was lowered to 5 °C for 0.5 hours. Centrifugal collection, water washing, freeze-drying.
[0050] (2) 5.0 g of PLA (M_n = 20,000 g / mol, T_g = 50 °C) was dissolved in 100 mL of dichloromethane. 1.0 g of the dried inner layer microcapsules obtained in step (1) was dispersed by ultrasonic treatment (100 W, 5 minutes). Solvent evaporation method coating: stirring at room temperature for 6 hours at 200 rpm. Vacuum drying (25 °C, 12 hours). Grinding and sieving, DR-PM-2 powder was obtained.
[0051] 3. Preparation of low toxicity nylon material modified composition (1) Raw material pretreatment: Bio-PA1010 (Mitsui Chemicals, Inc.) was vacuum dried at 85°C for 16 hours. TA-NC-2 and DR-PM-2 were vacuum dried at 50°C for 4 hours. Citric acid (monohydrate, food grade) was used as received. Carnauba wax (T1 grade) was used as received. 6200) was vacuum dried at 85°C for 16 hours. TA-NC-2 and DR-PM-2 were vacuum dried at 50°C for 4 hours. Citric acid (monohydrate, food grade) was used as received. Carnauba wax (T1 grade) was used as received.
[0052] (2) Component batching (in weight percent): Bio-PA1010: 90.0 wt% TA-NC-2: 2.0 wt% DR-PM-2: 3.0 wt% Citric acid: 0.1 wt% Carnauba wax: 0.2 wt% (3) Mixing: All the above components were placed in a high speed mixer and mixed at 800 rpm for 8 minutes.
[0053] (4) Twin-screw extrusion blending: A co-rotating twin-screw extruder (L / D = 40) was used. The temperature settings (from the feeding port to the die) were 185°C / 195°C / 205°C / 210°C / 215°C / 210°C (vacuum vent, vacuum level 0.08 MPa) / 205°C / 200°C. The screw rotation speed was 180 rpm.
[0054] (5) Cooling and pelletizing: The extruded strands were cooled in a water tank (water temperature 15°C) and cut into 2 mm length pellets by a pelletizer.
[0055] (6) Finished product drying: The obtained pellets were vacuum dried at 75°C for 6 hours.
[0056] Example 3: 1. Preparation of surface functionalized nanochitosan (TA-NC-3) (1) 5.0 g of chitosan (deacetylation degree 95%, viscosity average molecular weight 3.0 x 10 5 Da) was dissolved in 1000 mL of 2.0% (v / v) acetic acid aqueous solution. Under 1000 rpm stirring, 1.5% (w / v) aqueous sodium tripolyphosphate solution was added dropwise with a mass ratio of TPP to chitosan of 1:4. Stirring was continued for 1.0 hour. Ultrasonic treatment (25 kHz, 400 W, 30 minutes, ice bath). Centrifugal collection, water washing.
[0057] (2) Disperse the wet chitosan nanoparticles (approximately 2.0 g dry weight) obtained in step (1) in 200 mL of isopropanol-water (volume ratio 4:1). Add 3.0 times the molar amount of chitosan amino groups in monochloroacetic acid. Add 30% (w / v) NaOH aqueous solution dropwise under ice bath to adjust the pH to 11.0. React in a water bath at 65°C for 6 hours. Adjust the pH to 7.0 with dilute hydrochloric acid and wash with ethanol.
[0058] (3) Disperse 1.0 g of dried N-carboxymethyl chitosan nanoparticles in 100 mL of MES buffer at pH 6.0. Add 1.5 times the molar amount of mono-6-amino-6-deoxy-β-cyclodextrin from the carboxyl groups of the N-carboxymethyl chitosan nanoparticles. Add 2.5 times the molar amount of EDC·HCl and 1.2 times the molar amount of NHS from the carboxyl groups. Stir at room temperature (30℃) in the dark for 36 hours. Dialyze and freeze-dry to obtain TA-NC-3 powder.
[0059] 2. Preparation of double-walled natural polyphenol microcapsules (DR-PM-3) (1) Weigh 10.0 g of gelatin and 10.0 g of gum arabic, and dissolve them separately in 200 mL of deionized water at 55 °C. Disperse 5.0 g of grape seed extract proanthocyanidins (OPC, polyphenol content ≥95%) in 50 mL of ethanol-water (volume ratio 1:1). Emulsify the OPC dispersion into the gelatin solution under 10000 rpm shear. Add the gum arabic solution. Adjust the pH to 4.2 with 10% (v / v) acetic acid and stir at 45 °C for 2 hours. Cool to 10 °C and maintain for 1.0 hour. Centrifuge, wash with water, and freeze dry.
[0060] (2) Dissolve 10.0 g PLA (Mn = 40,000 g / mol, Tg = 60 °C) in 200 mL of dichloromethane. Add 3.0 g of the dried inner layer microcapsules obtained in step (1) and disperse by ultrasonication (200 W, 15 min). Coating by solvent evaporation: stir at 600 rpm for 12 hours at room temperature. Vacuum dry (40 °C, 24 h). Grind and sieve to obtain DR-PM-3 powder.
[0061] 3. Preparation of modified compositions for low-toxicity nylon materials (1) Raw material pretreatment: Bio-PA11 ( BMNO P40 TLD was vacuum dried at 95°C for 20 hours. TA-NC-3 and DR-PM-3 were vacuum dried at 60°C for 6 hours. Citric acid (monohydrate, food grade) was used as is. Calcium stearate (pharmaceutical grade) was dried at 70°C for 3 hours. Biocompatible masterbatch (PA11-based carrier, black) was dried at 80°C for 4 hours.
[0062] (2) Component composition (by weight percentage): Bio-PA11: 70.0 wt% TA-NC-3: 10.0 wt% DR-PM-3: 15.0 wt% Citric acid: 0.5 wt% Calcium stearate: 1.0 wt% Bio-compatible color masterbatch: 2.0 wt% (3) Mixing: Put all the above components into a high-speed mixer and mix at 1500 rpm for 15 minutes.
[0063] (4) Twin-screw extrusion blending: Use a co-rotating twin-screw extruder (L / D = 48). The temperature settings for each zone (from the feeding port to the die) are 200°C / 210°C / 225°C / 230°C / 230°C / 225°C (vacuum exhaust port, vacuum degree 0.09 MPa) / 220°C / 220°C. The screw rotation speed is 280 rpm.
[0064] (5) Cooling and pelletizing: The extruded strip is cooled in a water tank (water temperature 35°C) and cut into 4 mm long particles by a pelletizer.
[0065] (6) Finished product drying: The obtained particles are dried in a vacuum at 85°C for 10 hours.
[0066] Comparative Example 1: Compared with Example 1, the difference is that the surface functionalized nanochitosan (TA-NC-1) is not included in the composition, and its weight percentage is replaced by Bio-PA11, i.e. the amount of Bio-PA11 is 87.4 wt%, and the rest of the components and the preparation method are the same.
[0067] Comparative Example 2: Compared with Example 1, the difference is that the double-walled material natural polyphenol microcapsule (DR-PM-1) is not included in the composition, and its weight percentage is replaced by Bio-PA11, i.e. the amount of Bio-PA11 is 93.4 wt%, and the rest of the components and the preparation method are the same.
[0068] Comparative Example 3: Compared with Example 1, the difference is that the interface synergistic locking agent (citric acid) is not included in the composition, and its weight percentage is replaced by Bio-PA11, i.e. the amount of Bio-PA11 is 81.7 wt%, and the rest of the components and the preparation method are the same.
[0069] Comparative Example 4: The difference compared with Example 1 is that the surface functionalized nanochitosan (TA-NC-1) is replaced by common nanochitosan without surface functionalization. The common nanochitosan is directly dried after nanofication treatment in Example 1, and the addition amount is still 6.0wt%, and the rest of the components and preparation methods are the same as Example 1.
[0070] Comparative Example 5: The difference compared with Example 1 is that the double-layer wall material natural polyphenol microcapsule (DR-PM-1) is replaced by a single-layer natural polyphenol microcapsule containing only inner wall material. The single-layer microcapsule is directly dried after preparation in Example 1, and the active core and the addition amount are still 12.0wt% (based on the whole microcapsule), and the rest of the components and preparation methods are the same as Example 1.
[0071] Comparative Example 6: The difference compared with Example 1 is that the addition amount of surface functionalized nanochitosan (TA-NC-1) in the composition is adjusted to 0.5wt%, and Bio-PA11 is correspondingly increased to 86.9wt%, and the rest of the components and preparation methods are the same.
[0072] Comparative Example 7: The difference compared with Example 1 is that the addition amount of double-layer wall material natural polyphenol microcapsule (DR-PM-1) in the composition is adjusted to 20.0wt%, and Bio-PA11 is correspondingly reduced to 73.4wt%, and the rest of the components and preparation methods are the same.
[0073] Comparative Example 8: The difference compared with Example 1 is that when preparing the surface functionalized nanochitosan (TA-NC-1), EDC·HCl and NHS are omitted in Example 1, that is, the N-carboxymethyl nanochitosan and the aminated β-cyclodextrin derivative are only physically mixed without covalent grafting reaction, and the rest of the components and preparation methods are the same as Example 1.
[0074] Comparative Example 9: The difference compared with Example 1 is that the common petroleum-based polyamide 6 (PA6) is used instead of the bio-based polyamide 11 (Bio-PA11), and the addition amount is still 81.4wt%, and the rest of the components and preparation methods are the same as Example 1.
[0075] Comparative Example 10: The difference compared with Example 1 is that in the double-screw extrusion blending step, the melting zone temperature is set to 190℃, and the rest of the process parameters and components are the same as Example 1.
[0076] Test Example 1: In vitro cytotoxicity test I. Purpose of the experiment The potential cytotoxicity of the leaching solution of the nylon material modified composition prepared in Example 1 and Comparative Examples 1-7 and Comparative Example 9 was evaluated on L929 fibroblast cells by in vitro cell culture method to evaluate the biocompatibility of the material.
[0077] II. Experimental materials and reagents Cell line: L929 mouse fibroblast cells (purchased from the Chinese Academy of Sciences Typical Culture Collection Committee Cell Bank).
[0078] Sample group: material particles prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6, Comparative Example 7, and Comparative Example 9.
[0079] Culture medium: DMEM high-sugar medium (containing 10% fetal bovine serum FBS, 100 U / mL penicillin, 100 μg / mL streptomycin).
[0080] Reagents: MTT (3-(4,5-dimethylthiazole-2)-2,5-diphenyl tetrazolium bromide, Sigma-Aldrich), dimethyl sulfoxide (DMSO, analytical pure).
[0081] Control: Negative control: blank control of culture medium.
[0082] Positive control: 0.1% (w / v) phenol solution as a positive toxicant.
[0083] Main instruments: CO2 incubator, clean bench, microplate reader, inverted microscope, high-pressure steam sterilization pot.
[0084] III. Experimental steps 1. Sample leaching solution preparation: a. Take the material particles of each sample group (Example 1, Comparative Examples 1-9), soak in 75% ethanol for 30 minutes, rinse with sterile PBS three times, and dry in a clean bench.
[0085] b. According to the extraction ratio specified in GB / T 16886.12-2017 (for example, for irregular particles, the sample can be estimated and unified at 0.2 g sample / mL medium or a surface area to volume ratio of 3 cm 2 / mL).
[0086] c. Place in a 37±1℃ constant temperature shaking incubator and dynamically leach for 24±2 hours (for example, 50-100 rpm / min).
[0087] d. After the end of the extraction, the extract was removed and centrifuged at 4000 rpm for 10 minutes, and the supernatant was taken. The supernatant was filtered through a 0.22 μm microporous filter to remove bacteria, and the 100% concentration extract of each sample group was obtained and stored at 4°C for later use. The negative control and positive control were treated in the same way (the positive control was filtered after being added to the culture medium).
[0088] 2. Cell culture and inoculation: a. L929 cells were routinely cultured and subcultured in DMEM high-sugar medium containing 10% FBS at 37°C and 5% CO2.
[0089] b. L929 cells in the logarithmic growth phase were digested with 0.25% trypsin-EDTA to prepare a cell suspension, and the cell concentration was adjusted to 1 x 10 5 cells / mL.
[0090] c. The cell suspension was inoculated into a 96-well cell culture plate at 100 μL per well (i.e., 1 x 10 4 cells per well), and the plate was incubated in a 37°C, 5% CO2 incubator for 24 hours to allow the cells to adhere and grow.
[0091] 3. Cell addition and treatment: a. After 24 hours, the original culture medium in the 96-well plate was discarded.
[0092] b. Experimental group: 100 μL of the 100% concentration extract of each sample group (Example 1, Comparative Examples 1-7, Comparative Example 9) was added to each well.
[0093] c. Control group: 100 μL of culture medium without samples was added to the negative control wells, and 100 μL of culture medium containing 0.1% phenol was added to the positive control wells.
[0094] d. Six parallel wells were set up for each group.
[0095] e. The 96-well plate was placed back in the 37°C, 5% CO2 incubator for continued incubation for 24 hours.
[0096] 4. MTT detection of relative growth rate (RGR) of cells: a. After 24 hours of incubation, the supernatant was carefully aspirated from each well, and 100 μL of serum-free medium (or PBS) containing 0.5 mg / mL MTT was added.
[0097] b. Incubation was continued in the incubator for 4 hours.
[0098] c. The MTT solution was carefully discarded, 150 μL of DMSO was added to each well, and the plate was placed on a shaker for low-speed shaking for 10-15 minutes to fully dissolve the formazan crystals.
[0099] d. Use the microplate reader to determine the optical density value (OD value) of each well at a wavelength of 570 nm, with 630 nm as the reference wavelength (if any).
[0100] 5. Result determination: a. Calculate the relative growth rate (RGR%) of cells = (OD 实验组 / OD 阴性对照组 ) x 100%.
[0101] b. Determine the cytotoxicity level according to RGR% (refer to GB / T 16886.5-2017): RGR≥100%: 0 level (no cytotoxicity) 75%≤RGR<100%: 1 level (slight cytotoxicity) 50%≤RGR<75%: 2 level (moderate cytotoxicity) 25%≤RGR<50%: 3 level (severe cytotoxicity) RGR<25%: 4 level (serious cytotoxicity) Generally, levels 0-1 are considered to pass the cytotoxicity test.
[0102] The experimental results are shown in Table 1: Table 1: Results of in vitro cytotoxicity test of each sample group (MTT method) From the experimental data in Table 1, we can conclude that: The low-toxicity nylon material modified composition prepared in Example 1 exhibits excellent cell compatibility, with an average cell relative growth rate (RGR) of 93.17%, rated as 1 level of slight cytotoxicity, indicating that the material has low in vitro cytotoxicity potential. This is mainly due to its unique multi-component synergistic design: first, the use of bio-based polyamide as the matrix, as shown in Comparative Example 9 (using petroleum-based PA6), the RGR is only 53.63% (2 level), which is much lower than Example 1, indicating that bio-based polyamide itself provides a good foundation for achieving low toxicity. More importantly, the introduction of surface-functionalized nanochitosan in Example 1, the special cavity structure formed by the β-cyclodextrin derivative grafted after N-carboxymethylation can effectively adsorb and fix the trace harmful small molecules that may migrate out of the material, such as residual monomers or degradation products, thereby significantly reducing the toxic effects on cells. Comparing Comparative Example 1 (without adding surface-functionalized nanochitosan, RGR is 72.07%, 2 level) and Comparative Example 4 (adding ordinary nanochitosan without functionalization, RGR is 64.60%, 2 level), both show that the introduction of this specific functional component in Example 1 and its fine surface chemical modification make a decisive contribution to reducing cytotoxicity.
[0103] The addition of the double-layer wall material natural polyphenol microcapsule also plays a positive role in the biological safety of the overall material. Although its main function is to provide antioxidant and skin soothing, its excellent biocompatible wall material (gelatin, gum arabic and biodegradable polyester) and effective coating of the active core avoid potential cell stimulation that may be caused by direct or excessive exposure of polyphenols. The RGR of Comparative Example 2 (without the addition of polyphenol microcapsules) is 79.20% (level 1), which is slightly lower than Example 1, indicating that the polyphenol microcapsule itself has good cell compatibility; while the decrease in the results of Comparative Example 5 (using single-layer wall material polyphenol microcapsules, RGR is 74.63%, level 2) may imply the importance of the double-layer wall material structure for stable coating, preventing premature or improper leakage of the contents, thereby maintaining low cytotoxicity. This structure ensures the stable presence of active ingredients without adversely affecting cells.
[0104] In addition, although the presence of the interfacial synergistic locking agent does not directly show a significant difference in this short-term cytotoxicity test (Comparative Example 1 vs. Comparative Example 3, RGR is 87.53%, level 1), its potential role in long-term fixation of functional components and reduction of their long-term migration is an important guarantee for maintaining the long-term biological safety of the material. At the same time, the concentration of functional components also has a significant impact on cytotoxicity: the cell compatibility of Comparative Example 6 (low content of surface-functionalized nanochitosan, RGR is 81.13%, level 1) is acceptable but slightly inferior to Example 1, while Comparative Example 7 (high content of double-layer wall material natural polyphenol microcapsules, RGR is 67.47%, level 2) shows a trend of increased cytotoxicity, which may be due to physical effects or increased leachate concentration caused by excessive additives. This in turn demonstrates the necessity of optimizing the content of each component in Example 1 for achieving optimal biocompatibility. In summary, the present application, through the selection of biobased substrates, combined with nanofillers with targeted adsorption function, biocompatible sustained-release microcapsules, and locking agents to ensure the stability of the components, and optimizing the content of each component, together constructs a low-cytotoxicity material system.
[0105] Test Example 2: In vitro antioxidant performance test I. Purpose of the experiment Through DPPH free radical scavenging ability and ABTS cationic radical scavenging ability tests, the in vitro antioxidant activity of the extract of the nylon material modified composition prepared in Example 1 and the related comparative examples (Comparative Example 2, Comparative Example 5, Comparative Example 7) is evaluated to verify the antioxidant function of the double-layer wall material natural polyphenol microcapsule in the composition of the present application.
[0106] II. Experimental materials and reagents Sample groups: material particles prepared in Example 1, Comparative Example 2, Comparative Example 5, Comparative Example 7.
[0107] Reagents: DPPH (1,1-diphenyl-2-picrylhydrazyl, Sigma-Aldrich).
[0108] ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt, Sigma-Aldrich).
[0109] Potassium persulfate (K2S2O8, analytical pure).
[0110] Absolute ethanol (analytical pure).
[0111] Phosphate buffer (PBS, pH 7.4).
[0112] Control: Blank control: absolute ethanol.
[0113] Positive control: Vitamin C (Vc, analytical pure).
[0114] Main instruments: ultraviolet-visible spectrophotometer (or enzyme label instrument with corresponding wavelength detection function), constant temperature water bath or incubator, vortex mixer, analytical balance.
[0115] III. Experimental steps 1. Sample extract preparation: a. Take the sample group material particles (Example 1, Comparative Example 2, Comparative Example 5, Comparative Example 7), sterilize the surface with 75% ethanol, then rinse with sterile water and dry.
[0116] b. Accurately weigh 0.5g of each sample and add it to 10mL of absolute ethanol, and extract at 37°C in the dark for 24 hours (e.g., 100rpm).
[0117] c. After the extraction is complete, centrifuge the extract at 4000rpm for 10 minutes, and take the supernatant as the sample extract for standby.
[0118] 2. DPPH radical scavenging capacity determination: a. DPPH solution preparation: accurately weigh DPPH, dissolve and dilute with absolute ethanol to prepare a 0.1mM DPPH ethanol solution, and store at 4°C in the dark. Before use, adjust the absorbance value at 517nm to be within the range of 0.70±0.05.
[0119] b. Sample reaction: take 2.0mL of sample extract (or different dilution concentrations of extract if IC50 needs to be determined), add 2.0mL of DPPH ethanol solution, and mix quickly.
[0120] c. Control settings: Sample blank group (A 样品空白) : Take 2.0 mL of sample extract, add 2.0 mL of absolute ethanol.
[0121] DPPH control group (A DPPH对照 ) : Take 2.0 mL of DPPH ethanol solution, add 2.0 mL of absolute ethanol.
[0122] d. The above mixture is reacted at room temperature (25±2℃) for 30 minutes in the dark.
[0123] e. Absorbance determination: The absorbance value of each group of solutions is determined at a wavelength of 517 nm. Each group has 3 parallel duplicate wells.
[0124] f. Clearance rate calculation: DPPH free radical scavenging rate (%) = [1-(A 样品 -A 样品空白 ) / A DPPH对照 ] x 100%; Where A 样品 is the absorbance after the sample and DPPH reaction.
[0125] 3. ABTS cation radical scavenging capacity determination: a. ABTS stock solution preparation: Mix equal volumes of 7 mM ABTS aqueous solution and 2.45 mM potassium persulfate aqueous solution, and place at room temperature in the dark for 12-16 hours to form ABTS cation radical (ABTS·+) stock solution.
[0126] b. ABTS working solution preparation: Before use, dilute the ABTS·+ stock solution with PBS buffer (pH 7.4) or absolute ethanol to an absorbance value at 734 nm within the range of 0.70±0.05.
[0127] c. Sample reaction: Take 0.2 mL of sample extract (or extract at different dilution concentrations), add 3.8 mL of ABTS·+ working solution, and mix quickly.
[0128] d. Control settings: Sample blank group (A' 样品空白 ): Take 0.2 mL of sample extract, add 3.8 mL of the corresponding dilution solvent.
[0129] ABTS control group (A' ABTS对照 ): Take 3.8 mL of ABTS·+ working solution, add 0.2 mL of the corresponding dilution solvent.
[0130] e. The above mixture is reacted at room temperature (25±2℃) for 6 minutes in the dark (or the optimal reaction time is determined according to the pre-experiment).
[0131] f.Absorbance measurement: The absorbance value of each group of solution was measured at 734 nm wavelength. Each group had 3 parallel replicates.
[0132] g. Clearance calculation: ABTS·+ radical clearance (%) = [1-(A' 样品 -A' 样品空白 ) / A' ABTS对照 ] x 100%; wherein A' 样品 is the absorbance after the sample reacted with ABTS·+.
[0133] 4. Positive control test: Using a known concentration of Vitamin C solution (e.g. prepared with absolute ethanol) instead of sample extract, following the above DPPH and ABTS measurement procedures, to verify the effectiveness of the experimental system.
[0134] The experimental results are shown in Table 2: Table 2: Results of in vitro antioxidant activity test of each sample group extract From the experimental data in Table 2, we can conclude that: The extract of the composition of the present application (Example 1) exhibited significant in vitro antioxidant activity, with an average clearance rate of 73.80% for DPPH radicals and 85.03% for ABTS cationic radicals. This excellent antioxidant performance is mainly due to the carefully designed double-walled material natural polyphenol microcapsules in the composition. These microcapsules have natural polyphenols (such as procyanidins or tea polyphenols) as the active core, which are themselves powerful radical scavengers, capable of neutralizing unstable radicals by providing hydrogen atoms or electrons, thereby blocking the oxidation chain reaction and protecting materials and contacting skin tissue from oxidative damage. The extract of Comparative Example 2 (without adding any polyphenol microcapsules) showed almost no antioxidant activity (DPPH clearance rate 10.87%, ABTS clearance rate 15.60%), which directly proves that the double-walled material natural polyphenol microcapsules are the main contributors to the antioxidant function of the composition of the present application.
[0135] The double-layer wall material structure is essential for achieving effective antioxidant function in the present application. As described in Example 1.2, the inner layer wall material (gelatin and gum arabic) first performs a preliminary encapsulation of natural polyphenols, protecting their chemical stability during processing and storage; more importantly, the outer layer of biodegradable polyester (such as PCL or PLA) not only further enhances protection, but also confers controllable release characteristics on the microcapsules. The antioxidant activity of Example 1 is significantly higher than that of Comparative Example 1 and Comparative Example 5 (single-layer wall material polyphenol microcapsules, DPPH clearance rate 44.73%, ABTS clearance rate 55.53%). This indicates that the double-layer wall material structure can more effectively protect the activity of polyphenols, and possibly achieve more effective release of active ingredients through the moderate swelling or degradation of the outer layer of wall material during extraction, thereby exerting stronger free radical scavenging capacity. This design ensures that natural polyphenols can be effectively released when needed, rather than prematurely inactivated or trapped in the base material.
[0136] The content of the functional component also affects the antioxidant performance of the material. Comparative Example 7 (double-layer wall material natural polyphenol microcapsules with a higher content of 20.0 wt%) shows the highest antioxidant activity (DPPH clearance rate 79.30%, ABTS clearance rate 89.67%), slightly higher than Example 1. This is as expected, i.e. within a certain range, increasing the content of antioxidant active ingredients can improve the overall antioxidant capacity. However, considering the processing performance, cost, and other biocompatibility indicators (such as the potential impact of cytotoxicity in Test Example 1), it is not necessarily the higher the better. The ratio of Example 1 (12.0 wt% DR-PM) not only provides significant antioxidant effect, but also balances other performance, reflecting the rationality and synergistic effect of the formulation design of the present application. The present application successfully imparts the antioxidant capacity of natural polyphenols to nylon materials through double-layer wall material microcapsule technology, providing additional protection for their use in skin contact applications.
[0137] Test Example 3: Functional component migration and release behavior test (simulated sweat) I. Purpose of the experiment Through the simulated sweat soaking experiment, the adsorption capacity of the material to specific indicator small molecules is determined, and the harmful substance fixation effect of the surface functionalized nanochitosan is indirectly evaluated.
[0138] Through the simulated sweat soaking experiment, the cumulative release amount of natural polyphenols in the material over time is determined, and the sustained release characteristics of the double-layer wall material natural polyphenol microcapsules and the stabilizing effect of the interfacial synergistic locking agent are evaluated.
[0139] II. Experimental materials and reagents
[0140] Simulated sweat: Acidic artificial sweat prepared according to ISO 105-E04 standard (e.g. L-histidine monohydrochloride monohydrate 0.5 g / L, sodium chloride 5 g / L, disodium hydrogen phosphate heptahydrate 2.5 g / L, pH adjusted to 5.5 with 0.1 M HC1).
[0141] Indicative small molecule: Methylene blue (MB, analytical grade), as a model pollutant that can be included by β-cyclodextrin.
[0142] Polyphenol detection reagent: Folin-Ciocalteu reagent, anhydrous sodium carbonate (analytical grade), gallic acid (analytical grade, as a standard).
[0143] Main instruments: constant temperature oscillation incubator, ultraviolet visible spectrophotometer, centrifuge, pH meter, analytical balance.
[0144] III. Experimental steps Part A: Specific small molecule adsorption residual test (simulated surface functionalized nanochitosan function) 1. Sample preparation: Take 1.0 g of sample group (Example 1, Comparative Example 3, Comparative Example 8) material particles, sterilize the surface with 75% ethanol, then rinse with sterile water and air dry.
[0145] 2. MB standard solution preparation: accurately weigh methylene blue, and prepare a 10 μg / mL MB standard solution with simulated sweat.
[0146] 3. Adsorption experiment: add 1.0 g of treated sample particles to 20 mL of 10 μg / mL MB simulated sweat solution.
[0147] 4. Control setting: 20 mL of 10 μg / mL MB simulated sweat solution without sample as a blank control.
[0148] 5. Place the sample bottle in a constant temperature oscillation incubator at 37±1°C, and oscillate at 100 rpm for 24 hours.
[0149] 6. Absorbance determination: after 24 hours, remove the solution, centrifuge at 4000 rpm for 10 minutes, and take the supernatant. Use an ultraviolet visible spectrophotometer to measure the absorbance of MB in the supernatant at the maximum absorption wavelength of methylene blue (about 664 nm).
[0150] 7. Adsorption rate calculation: MB adsorption rate (%) = [(A 空白 -A 样品 ) / A 空白 ] x 100% (wherein 空白 is the absorbance of the blank control group MB solution, A样品 Three parallel holes were set for each group of sample treatment supernatant MB solution absorbance.
[0151] Part B: Natural polyphenol release test 1. Sample preparation: Take 2.0 g of sample particles from each sample group (Example 1, Comparative Example 3, Comparative Example 5, Comparative Example 10), and after surface sterilization with 75% ethanol, rinse with sterile water and air dry.
[0152] 2. Release experiment: Add 2.0 g of treated sample particles to 50 mL of simulated sweat.
[0153] 3. Place the sample bottle in a constant temperature shaking incubator at 37±1°C, and shake at 50 rpm.
[0154] 4. Sampling: At 1 h, 4 h, 8 h, 12 h, 24 h, and 48 h, respectively, take 2 mL of release medium (simulated sweat) from each sample bottle, and immediately supplement with an equal volume of fresh simulated sweat. The removed sample liquid is filtered through a 0.45 μm filter membrane before testing.
[0155] 5. Total polyphenol content determination (Folin-Ciocalteu method): a. Standard curve preparation: Prepare a series of gallic acid standard solutions with different concentrations (e.g. 0, 10, 20, 40, 60, 80, 100 μg / mL). Take 0.5 mL of each concentration of standard solution, add 2.5 mL of Folin-Ciocalteu reagent (diluted 10 times), mix well, and stand for 5 minutes. Add 2.0 mL of 7.5% (w / v) Na2CO3 solution, mix well, and react at 50°C in a water bath for 5 minutes, or at room temperature in the dark for 1 hour. Measure the absorbance at 765 nm, and plot the standard curve.
[0156] b. Sample determination: Take 0.5 mL of the sample release liquid to be tested (dilute appropriately if necessary), and follow the same procedure as the standard curve preparation step above to measure the absorbance.
[0157] c. Calculate the total polyphenol concentration in the sample release liquid (in gallic acid equivalent μg / mL GAE) according to the standard curve.
[0158] 6. Cumulative release rate calculation: Cumulative release amount (μg) = C n V0+Σ(C i V i )(i = 1 ~ n-1) (where C n is the polyphenol concentration measured at the nth sampling, V0 is the total volume of release medium, C i is the polyphenol concentration measured at the ith sampling, and V iAssuming the total polyphenol content in the material is known (previously determined by complete extraction method, or calculated based on formulation theory and corrected), the cumulative release percentage can be calculated. For simplicity, the cumulative release amount or concentration at different time points can be directly compared here. Each group has 3 parallel duplicate wells.
[0159] The experimental results are shown in Table 3: Table 3: Test results of functional component migration and release behavior (simulated sweat) From the experimental data in Table 3, we can get: The composition of the present application (Example 1) exhibits excellent harmful substance adsorption capacity and good active ingredient release performance in a simulated sweat environment. The data shows that the adsorption rate of Example 1 to the simulated pollutant methylene blue reaches 72.8%, which is mainly due to the inclusion of surface functionalized nanochitosan. After N-carboxymethylation, the nanochitosan is covalently grafted with amino β-cyclodextrin derivative, forming a large number of β-cyclodextrin structures with hydrophobic inner cavity and hydrophilic outer edge on the surface of nanochitosan. These unique molecular cavities can selectively capture and fix small-molecule organic substances such as methylene blue through host-guest interactions, thereby reducing their free movement in the material and migration to the outside. The methylene blue adsorption rate of Comparative Example 8 (which omits the key covalent grafting step in the preparation of surface functionalized nanochitosan) is significantly reduced to 31.2%, fully demonstrating the key role of successful grafting and stable existence of β-cyclodextrin derivative in achieving high-efficiency adsorption function.
[0160] In terms of the release behavior of active polyphenols, Example 1 exhibits a smooth and sustained release curve, with a cumulative release of 8.5 μg GAE / mL and 12.1 μg GAE / mL of polyphenols at 24 hours and 48 hours, respectively. This is due to the ingenious structure of the double-layer wall material natural polyphenol microcapsule and the stabilizing effect of the interfacial synergistic locking agent. The double-layer wall material (inner layer gelatin / arabic gum, outer layer biodegradable polyester) not only protects the activity of natural polyphenols, but more importantly, regulates their release rate. The outer layer of polyester wall material slowly swells or degrades under the mild conditions of simulated sweat, allowing the internal polyphenols to be released in a gradual manner. Comparative Example 5 (which uses single-layer wall material polyphenol microcapsules) has a cumulative release concentration of 15.9 μg GAE / mL and 22.8 μg GAE / mL at 24 hours and 48 hours, respectively, with an initial release rate significantly higher than Example 1. This indicates that the single-layer wall material has weak binding ability for polyphenols, making it difficult to achieve long-term sustained release.
[0161] The interfacial synergistic lock agent plays a key role in stabilizing the functional component and preventing its premature loss in the present application. Compared with Example 1 and Comparative Example 3 (without the addition of an interfacial synergistic lock agent), the polyphenol release of Comparative Example 3 is more rapid and the total amount is higher (18.3 pg GAE / mL at 24 h, 25.7 pg GAE / mL at 48 h), which suggests that in the absence of a lock agent, the combination of polyphenol microcapsules and surface-functionalized nanochitosan (although the MB adsorption rate has little difference in this short-term test, the long-term stability may be affected) and the nylon matrix is not firm enough, and it is easier to fall off or rapidly release its contents under the soaking conditions. In addition, the processing technology also has a certain influence on the release behavior, such as Comparative Example 10 (using a lower extrusion temperature), the polyphenol release concentration (11.8 pg GAE / mL at 24 h, 16.5 pg GAE / mL at 48 h) is between Example 1 and Comparative Example 3, indicating that improper processing conditions may not be able to fully play the role of the lock agent or affect the integrity of the microcapsules. Therefore, through the synergistic effect of the functional filler with a specific structure, precise microcapsule coating technology, and interfacial enhancement strategy, the present application realizes the effective fixation of harmful substances and the controlled release of beneficial active ingredients.
[0162] While embodiments of the present application have been shown and described, it is to be understood that various modifications, substitutions, replacements and variations can be made to these embodiments without departing from the principles and spirit of the present application, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A low-toxicity nylon material modified composition, characterized in that, The composition comprises, by weight percentage: 70–90 wt% bio-based polyamide; 2-10 wt% of surface-functionalized chitosan nanoparticles, wherein the surface-functionalized chitosan nanoparticles are prepared by N-carboxymethylating chitosan nanoparticles and then covalently grafting them with an amino-based β-cyclodextrin derivative; 3-15 wt% of double-walled natural polyphenol microcapsules, wherein the inner wall material of the double-walled natural polyphenol microcapsules is gelatin and gum arabic, the active core is natural polyphenols, and the outer wall material is biodegradable polyester. 1–0.5 wt% of an interfacial synergistic locking agent, wherein the interfacial synergistic locking agent is selected from citric acid or its derivatives.
2. The low-toxicity nylon material modified composition according to claim 1, characterized in that, The bio-based polyamide is selected from at least one of bio-based polyamide 11 or bio-based polyamide 1010.
3. The low-toxicity nylon material modified composition according to claim 1, characterized in that, The amino-modified β-cyclodextrin derivative is mono-6-amino-6-deoxy-β-cyclodextrin.
4. The low-toxicity nylon material modified composition according to claim 1, characterized in that, The natural polyphenols are selected from at least one of grape seed extract proanthocyanidins or green tea extract tea polyphenols; the biodegradable polyester is selected from at least one of polycaprolactone or polylactic acid.
5. The low-toxicity nylon material modified composition according to claim 1, characterized in that, The composition further includes 0.2 to 1.0 wt% of a biocompatible lubricant and / or 0 to 2.0 wt% of a biocompatible masterbatch.
6. A method for preparing a low-toxicity nylon material modified composition according to any one of claims 1-5, characterized in that, Includes the following steps: (i) A mixture of bio-based polyamide, surface-functionalized nano-chitosan, bilayer wall material natural polyphenol microcapsules and interfacial synergistic locking agent, together with optional biocompatible lubricant and / or biocompatible masterbatch, is obtained. (ii) The mixture is melt-blended and extruded into granules using a twin-screw extruder.
7. The preparation method according to claim 6, characterized in that, In step (ii), the temperature of the melting zone of the twin-screw extruder is controlled at 210–230°C, and a vacuum exhaust is provided at the rear of the melting section.
8. The preparation method according to claim 6, characterized in that, Before step (i), the following steps are also included: (a1) N-carboxymethylation of nano-chitosan was performed to obtain N-carboxymethyl nano-chitosan; (a2) The N-carboxymethyl nano-chitosan was covalently grafted with an amino-β-cyclodextrin derivative under EDC·HCl and NHS catalysis to obtain surface-functionalized nano-chitosan. (b1) Natural polyphenols were encapsulated with gelatin and gum arabic as inner wall materials by complex coagulation method to obtain inner polyphenol microcapsules; (b2) The inner polyphenol microcapsules are coated with the outer wall material biodegradable polyester to obtain the double-wall natural polyphenol microcapsules.
9. The use of a low-toxicity nylon material modified composition according to any one of claims 1-5 in the preparation of skin contact articles.
10. The application according to claim 9, characterized in that, The skin contact product is an elastic webbing of a watch strap, a smart wearable device wristband, or close-fitting clothing.
Citation Information
Cited By
Automotive interior carpet and preparation method thereof
CN121471653A